The Act on shaping the agricultural system – selected axiological aspects - Zięty, Jakub Jan; Kudrzycka-Szypiłło, Aleksandra (Przegląd Prawa Rolnego, 2025)
This article assesses the implementation of the provisions of the Act on shaping the agricultural system and the values ​referred to in the preamble to this Act and in Article 23 of the Constitution of the Republic of Poland. To achieve such a defined goal, the authors first assess the axiological foundations of the Act and then move on to the its analysis. Next they analyse the issues related to the scope and function of the preamble and the implementation of the values to which it refers. Based on the analysis they conclude that the legislator did not provide for the implementation of the axiological assumptions arising from the constitutional principle that the shape of the agricultural system should be based on family farms. At the same time, they draw attention to the evident lack of appropriate regulations regarding family farms as well as their incorrect definition.